The Impact of Activity Based Costing (ABC) on Cost Reduction - Qabil Zrar Hamad; Khalis Mheadin Qadir; Muhamad Khoshawi Mustafa; Muhamad Azad Azeez; Shifa Arif Omer (Zanco Journal of Humanity Sciences)
This study examines the impact of Activity-Based costing technique (ABC) on cost reduction and competitive price in the number of industrial firms in Erbil city in the Kurdistan Region- Iraq. The objective of the study investigates the impact of activity-based costing technique on cost reduction and competitive price. This study used quantitative method for determine and describe results and a survey questionnaire for collecting data on manufacturing firms in Erbil city, Kurdistan region of Iraq. Also. Randomly distributed 125 questionnaire forms on specific employees and collecting 87 forms. This research study used the Statistical Package for the Social Sciences (SPSS 26) software program to analyze collected data. The study also tested the correlation and simple regression models. The results provided a significant relationships and impact exist between activity-based costing technique with cost reduction and significant relationship and significant impact with competitive price. The model was approved to give a clear reliability test by applying alpha Cronbach test. Moreover, the study model constructs to explain the concern relationship between activity-based costing technique and product value.